Deep convolutional neural network-based automated segmentation of the maxillofacial complex from cone-beam computed tomography:A validation study. (September 2022) - Preda, Flavia; Morgan, Nermin; Van Gerven, Adriaan; Nogueira-Reis, Fernanda; Smolders, Andreas; Wang, Xiaotong; Nomidis, Stefanos; Shaheen, Eman; Willems, Holger; Jacobs, Reinhilde
Abstract: Objectives: The present study investigated the accuracy, consistency, and time-efficiency of a novel deep convolutional neural network (CNN) based model for the automated maxillofacial bone segmentation from cone beam computed tomography (CBCT) images. Method: A dataset of 144 scans was acquired from two CBCT devices and randomly divided into three subsets: training set ( n  = 110), validation set ( n  = 10) and testing set ( n  = 24). A three-dimensional (3D) U-Net (CNN) model was developed, and the achieved automated segmentation was compared with a manual approach. Results: The average time required for automated segmentation was 39.1 s with a 204-fold decrease in time consumption compared to manual segmentation (132.7 min). The model was highly accurate for identification of the bony structures of the anatomical region of interest with a dice similarity coefficient (DSC) of 92.6%. Additionally, the fully deterministic nature of the CNN model was able to provide 100% consistency without any variability. The inter-observer consistency for expert-based minor correction of the automated segmentation observed an excellent DSC of 99.7%. Conclusion: The proposed CNN model provided a time-efficient, accurate, and consistent CBCT-based automated segmentation of the maxillofacial complex. Clinical significance: Automated segmentation of the maxillofacial complex could act as an alternative to the conventional segmentation techniques for improving the efficiency of the digital workflows. This approach could deliver accurate and ready-to-print3D models, essential to patient-specific digital treatment planning for orthodontics, maxillofacial surgery, and implant dentistry. Graphical abstract: Image, graphical abstract